URGENSI PENANAMAN NILAI-NILAI PENDIDIKAN ISLAM BAGI REMAJA LEWAT KISAH-KISAH ISLAMI - Muksin, Muksin; Mudlofir, Ali (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2024)
Islamic education in the past, had an important role in shaping the character and morality of adolescents. In addition to the awareness from parents of the importance of instilling Islamic education for a child from an early age, adolescents also have an interest and awareness of the importance of studying, including religious knowledge. Nevertheless, the reality of our youth is far from the values of Islamic education. Even our teenagers today tend to fall into negativity and away from religious teachings. In this study, there were two formulations of the problem raised. Namely the strategy of instilling Islamic educational values for adolescents and the urgency of instilling Islamic educational values for adolescents through Islamic stories. The method used in this study is qualitative research methodology with a Library Research approach, which is reviewing books and journals that have been published in accordance with the theme. The results of the study, namely the cultivation of Islamic educational values for adolescents, can be done by prioritizing 3 aspects, namely monotheism / religion, moral aspects, and social aspects. Meanwhile, the urgency of its application can be done by prioritizing the cultivation of Islamic education values for adolescents through Islamic stories whose application can be more effective in providing a more comprehensive religious understanding.